Case Report: Application and Limitations of a Plant-Based Diet Formulated for a Cat With Feline Lower Urinary Tract Disease - Dodd, Sarah A. S.; Grant, Caitlin; Abood, Sarah K.; Verbrugghe, Adronie (Frontiers in Veterinary Science, 2021)
A 2-year-old male castrated domestic shorthair cat was presented for recommendations for dietary management of chronic FLUTD using a strictly plant-based diet. The cat had a history of urethral obstruction of unknown aetiology, persistent marked struvite crystalluria and persistent inappropriate elimination. Commercial plant-based products meeting the nutritional recommendations for maintenance of adult cats with the lowest concentration of struvite precursors were identified, but the cat would not eat them. At the request of the client, a homemade plant-based diet was formulated with the intention of increasing water intake and promoting acidic, dilute urine. Urine concentration was able to be decreased somewhat and struvite crystalluria resolved, but the urine remained more alkaline than intended. The cat clinically improved and no further FLUTD episodes were reported by the client.